Hubungan Sanitasi Lingkungan Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Sambirejo Rejang Lebong Tahun 2025 - Sutarni Sutarni; Sasteri Yulianti; Hengki Tranado (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
World Health Organization (2019) diarrhea is an environmentally-based disease that occurs in almost all geographical areas of the world. Diarrhea is the third leading cause of death in children aged 1-59 months. Globally, the WHO (World Health Organization) states that there are approximately 1.7 billion cases of diarrhea in children each year. More precisely, every year diarrhea kills around 443,832 children aged under 5 and an additional 50,851 children (WHO, 2024). The purpose of this study is to determine a correlation between environmental sanitation and the incidence of diarrhea in toddlers in the Working Area of Sambirejo Health Center, Rejang Lebong in 2025. The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 72 people. The results of the univariate analysis showed that almost all respondents (38.9%) had an inadequate source of clean water, almost all respondents (29.2%) did not have access to a healthy toilet, almost all respondents (37.5%) had poor waste management, almost all respondents (43.1%) had poor sewage management, and nearly half of the respondents (36.1%) had poor wastewater management. The results of the bivariate analysis showed a correlation between clean water sources (0.000), sanitary toilets (p=0.000), waste management (p=0.002), and wastewater management (p=0.004) with the incidence of diarrhea in toddlers. There is a correlation between environmental sanitation and the incidence of diarrhea in toddlers in the Working Area of Sambirejo Health Center, Rejang Lebong in 2025. The Health Center is expected to enhance its routine environmental health education programs for the community, particularly mothers with infants.